w-30=2(w-6)

Simple and best practice solution for w-30=2(w-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w-30=2(w-6) equation:



w-30=2(w-6)
We move all terms to the left:
w-30-(2(w-6))=0
We calculate terms in parentheses: -(2(w-6)), so:
2(w-6)
We multiply parentheses
2w-12
Back to the equation:
-(2w-12)
We get rid of parentheses
w-2w+12-30=0
We add all the numbers together, and all the variables
-1w-18=0
We move all terms containing w to the left, all other terms to the right
-w=18
w=18/-1
w=-18

See similar equations:

| H(t)=-16t²+80t+0 | | –70=–2r | | 43x+5=17 | | 3(x-3)=4(x+7)-5 | | (-5x-7)-(13+4x)=-9x-20 | | 6|3-2x|+5=11 | | 3(x+8)=12(12-x) | | 9(2c+3)=99 | | 6(m-1m)=3(3m+5) | | x+12=4x+13 | | -5.58+3.7k=16.99 | | -40=5(3x-2) | | 10x=25x5 | | 4q=14 | | x+3/4=5/10 | | 3(a-3)=-6a-(3a+9) | | –4/5(9x–20)–3x=45x–6 | | 15x=5x=25 | | 3x+12=4x-15 | | x²+14x=-46 | | z+4=10.47 | | 0.3(y+2=-6.3 | | x+7/9=5 | | 4(y-7)=7y-1 | | 3(2+5x)=x=3 | | 8(v−87)=96 | | -32=-2a+6 | | 5+4y=34 | | 1/2(c+1)=5 | | −3/1​=j/4​−3/10​ | | 1=3+m/12 | | -5+10x=-2x+1 |

Equations solver categories